Biomechanical investigation of tibial tubercle osteotomy fixed with various screw configurations. Issue 2 (February 2019) - Chang, Chih-Wei; Chen, Yen-Nien; Li, Chun-Ting; Chung, Chi-Rung; Tseng, Chung‐Chih; Chang, Chih-Han; Peng, Yao-Te
Highlights: The superior cutting plane plays an important role in the stability of the TTO. The configuration of two parallel downward screws provides the best stability. The configuration of two parallel upward screws is not recommended for the fixation of TTO. Abstract: Introduction: To date, the effects of various screw configurations on the stability of tibial tubercle osteotomy (TTO) are not completely understood. Hence, the first aim of this study is to evaluate the stability of TTO under various screw configurations. The second aim is to evaluate the internal stresses in the bone and the contact forces on the bone fragment that are developed by the tibia and screws in response to the applied load after the equilibrant is revealed. Methods: To calculate the biomechanical responses of the bone and screw under loading, finite element (FE) method was used in this study. Six types of screw configurations were studied in the simulation: two parallel horizontal screws placed at a 20 mm interval, two parallel horizontal screws placed at a 30 mm interval, two parallel upward screws, two parallel downward screws, two trapezoid screws, and two divergent screws. The displacement of the bone fragment, contact forces on the fragment, and the internal stress in the bone were used as indices for comparison. Results: Among all configurations, the configuration of two parallel downward screws yielded the highest stability with the lowest fragment displacement and gap opening. Although the maximum displacement of the TTO with the configuration of two parallel horizontal screws was slightly higher than that of the downward configuration, the difference was only 0.2 mm. The configuration of two upward screws resulted in the highest fragment displacement and gap deformation between the fragment and tibia. The stress of the osteotomized bone fragment was highest with the configuration of two upward screws. Conclusion: Based on the present model, the current configuration of two parallel horizontal screws is recommended for TTO. If this is inappropriate in a specific clinical scenario, then the downward screw configuration may be used as an alternative. By contrast, the configuration of two parallel upward screws is least suggested for the fixation of TTO.